2011
DOI: 10.1002/bio.1363
|View full text |Cite
|
Sign up to set email alerts
|

Effect of colloidal β‐cyclodextrins–Fe3O4 magnetic nanoparticles on the chemiluminescence enhancement of luminol–Ag(III) complex for rapid and sensitive determination of cysteine in human serum

Abstract: Colloidals solution of Fe3 O4 magnetic nanoparticles (MNPs), capped with β-cyclodextrins (β-CD) as inclusion complexes, were found to enhance the chemiluminescence (CL) intensity of the luminol-diperiodatoargentate(III) (DPA) system. On injection of cysteine into the luminol-DPA-β-CD-Fe3 O4 MNPs inclusion complexes system, the CL intensity is strongly enhanced. The enhanced CL signal is ascribed to the catalytic effect of Fe3 O4 MNPs capped with β-CD, which is assumed to stabilize the CL intermediate. Based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…(Balikungeri et al, 1977). The Ag(III) complex was characterized by UV-visible spectra on a model 8453 spectrophotometer (Agilent, USA), exhibiting two absorb peaks at 252 and 362 nm, in agreement with the values reported earlier (Rezaei et al, 2012;Masse and Simon, 1982). The Ag(III) complex was used freshly daily.…”
Section: Experimental Chemicals and Reagentssupporting
confidence: 66%
See 2 more Smart Citations
“…(Balikungeri et al, 1977). The Ag(III) complex was characterized by UV-visible spectra on a model 8453 spectrophotometer (Agilent, USA), exhibiting two absorb peaks at 252 and 362 nm, in agreement with the values reported earlier (Rezaei et al, 2012;Masse and Simon, 1982). The Ag(III) complex was used freshly daily.…”
Section: Experimental Chemicals and Reagentssupporting
confidence: 66%
“…Some studies have demonstrated that the oxidation of luminol by the Ag(III) complex can generate CL in alkaline, which has been used to quantify 6-mercaptopurine (Sun et al, 2013), dopamine (Xu et al, 2011), 10-hydroxycamptothecin , cysteine (Rezaei et al, 2012) and cortisol (Shi et al, 2009) by a flow-injection CL method in blood samples and pharmaceutical preparations. Some studies have demonstrated that the oxidation of luminol by the Ag(III) complex can generate CL in alkaline, which has been used to quantify 6-mercaptopurine (Sun et al, 2013), dopamine (Xu et al, 2011), 10-hydroxycamptothecin , cysteine (Rezaei et al, 2012) and cortisol (Shi et al, 2009) by a flow-injection CL method in blood samples and pharmaceutical preparations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, direct determination of cysteine in plasma was not successful. Therefore, according to Rezaei et al, 60 a deproteination process was carried out by using acetone and the standard addition was carried out by spiking known amounts of cysteine standard solution to plasma samples. For the release of cysteine which is bound to protein in plasma, 10.0 mL b-mercaptoethanol was added to 2.0 mL of the plasma.…”
Section: Applicationmentioning
confidence: 99%
“…have been reported to enhance CL reactions. [ 15–25 ] Metal nanoclusters (NCs) are composed of several to dozens of metal atoms, and commonly have an ultra‐small size of < 2 nm. [ 26 ] Compared with metal nanoparticles, metal nanoclusters are smaller in size and have a larger specific surface area.…”
Section: Introductionmentioning
confidence: 99%